Informed Consent in Otolaryngologic Surgery: Case Scenario from a Nigerian Specialist Hospital - O. A. Afolabi; J. O. Fadare; O. T. Ajiboye (Case Reports in Otolaryngology)
Informed consent is a foundational concept necessary for ethical conduct of clinical research and practice. It is a technical tool that shifts the autonomy to decide whether a medical procedure should be performed—from the doctor to the patient. However there is an ongoing discussion in bioethical circles on the level of comprehension of the informed consent process by the patients and research participants. We present this case vignette and the discussion afterwards to explore the question of to what extent a patient comprehends the information given to him/her before a surgical procedure is carried out. In other words, the question being asked here is how informed is informed consent in the context of oto-laryngological practice.